A comparative study of low-pressure pneumoperitoneum versus standard-pressure pneumoperitoneum in laparoscopic cholecystectomy in tertiary care center - Ramesh Chandra Arun,; Kuldeep Kumar, (Asian Journal of Medical Sciences, 2024)
Background: Laparoscopic cholecystectomy is the gold standard management of symptomatic cholelithiasis. We try to use low-pressure pneumoperitoneum (LPP) to study the effect of pneumoperitoneum in the duration of surgery, field of visualization with providing sufficient work space for surgeon, and post-operative shoulder pain and hospital stay in laparoscopic cholecystectomy. Aims and Objectives: The aims and objectives of the study are to compare outcomes in LPP versus standard-pressure pneumoperitoneum (SPP) with respect to duration of surgery, CO2 consumption, field of visualization, and surgical difficulties to convert SPP or open cholecystectomy and post-operative shoulder pain and hospital stay. Materials and Methods: The prospective randomized study was conducted in tertiary care center, Government Medical College, Banda, Uttar Pradesh from July 2021 to October 2022. All consented 100 patients after randomization were allotted into two groups. Results: In our study, the mean duration of surgery surgical difficulties to convert open and standard pressure and difficulty in field visualization insignificant is more in LPP as compared to SPP but CO2 consumption, post-operative shoulder pain, and mean hospital stay is less in LPP as compared to SPP. Conclusion: Laparoscopic cholecystectomy in LPP is safe and feasible. Field visualization, conversion rate, and duration of surgery are affected non-significantly because depend on the expertise of surgeon but shoulder pain, CO2 consumption, and hospital stay are less in LPP.